2019
DOI: 10.1177/0363546519872975
|View full text |Cite
|
Sign up to set email alerts
|

Bone Bruise and Anterior Cruciate Ligament Tears: Presence, Distribution Pattern, and Associated Lesions in the Pediatric Population

Abstract: Background: Bone bruise characteristics after anterior cruciate ligament (ACL) injury have been correlated with the level of joint derangement in adults. However, the literature lacks information about younger patients, whose higher ligamentous laxity may lead to different lesion patterns. Purpose: To investigate the prevalence, size, location, and role of bone bruise associated with ACL rupture in the pediatric population. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Knee magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 38 publications
3
38
5
Order By: Relevance
“…Numerous studies 1,5,32,33 have found relationships between lateral bone bruises and tears of the lateral meniscus. No definitive consensus exists as Bordoni et al 7 and Novaretti et al 37 did not find a relationship between bone bruises and any meniscal lesion. Of practical consideration, these 2 studies were performed in pediatric populations.…”
Section: Associated Injuriesmentioning
confidence: 93%
See 3 more Smart Citations
“…Numerous studies 1,5,32,33 have found relationships between lateral bone bruises and tears of the lateral meniscus. No definitive consensus exists as Bordoni et al 7 and Novaretti et al 37 did not find a relationship between bone bruises and any meniscal lesion. Of practical consideration, these 2 studies were performed in pediatric populations.…”
Section: Associated Injuriesmentioning
confidence: 93%
“…Recent studies into the distribution of bone bruises within the knee found a wide range: between 48.3% and 91.7% of ACL tears had a bruise of the lateral femoral condyle (LFC) (Figure 1), 1,5,7,8,12,26,27,31,35,44,46 between 49.4% and 97.6% of the lateral tibial plateau (LTP) (Figure 1), 1,5,7,8,12,26,27,31,35,44,46 between 12.5% and 53% of the medial femoral condyle (MFC) (Figure 2), 1,7,8,12,26,27,44,46 and between 12.4% and 83.5% of the medial tibial plateau (MTP) (Figure 3). 1,7,8,12,26,27,31,44,46 Consistently, lateral contusions are more prevalent than medial contusions, and tibial contusions are more prevalent than femoral contusions. Shi et al 44 and Bordoni et al 7 identified bone bruise locations in the sagittal plane and found bone bruises primarily in the posterior compartment of the tibia and the central or anterior compartments of the femur.…”
Section: Mechanisms Of Bone Bruisesmentioning
confidence: 99%
See 2 more Smart Citations
“…Paediatric patients may be at increased risk of developing meniscal tears due to increased joint laxity. 23 However, a study with level I evidence showed that the number of children and adolescents diagnosed with ramp lesion in ACL-deficient knee does not exceed that of adults, reaching 23%. 24 …”
Section: Risk Factorsmentioning
confidence: 98%